PENERAPAN LOGIKA FUZZY TSUKAMOTO BERBASIS WEB UNTUK KLASIFIKASI DAERAH RAWAN KECELAKAAN DI KOTA JAMBI - Suana, Irma; Surya, Junaidi (FORTECH (Journal of Information Technology), 2024)
This study aims to apply web-based Tsukamoto fuzzy logic in the classification of accident areas in Jambi City. This method was developed by researchers at POLSERSTA Jambi city with the aim of increasing understanding of the risks of traffic accidents and helping make more effective decisions. Tsukamoto's fuzzy logic was chosen because of its ability to deal with uncertainty in the context of a classification involving various factors. The proposed system is able to take input data such as traffic levels, weather conditions, and road types, and convert them into a risk classification using fuzzy logic. The results of this system can provide guidance for traffic security officers and related agencies in managing potential accident areas. This research shows that web-based Tsukamoto fuzzy logic has the potential to be a useful tool in identifying traffic accident risk areas. However, improvements in data validation, optimization of fuzzy models, and collaboration with related parties need to be made to ensure the accuracy and usefulness of this system in improving traffic safety in Jambi City